Nilai-Nilai Pendidikan Islam Dalam Film Bidadari Bermata Bening Karya Habiburrahman El Shirazy - Venina Dwita Kusuma (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ISLAMIC EDUCATIONAL VALUES IN THE FILM "BEN-EYED ANGEL" BY HABIBURRAHMAN EL SHIRAZY Film can be an effective means of conveying valuable messages about the values ​​of Islamic Religious Education, allowing us all to draw profound wisdom and lessons from the stories presented. Thus, this film is not only entertaining but also makes a positive contribution to shaping our character and spirituality as better and more faithful individuals. Let us use this film as inspiration to increase awareness and practice of Islamic values ​​in our daily lives. This journal uses a literature review research method. The data collection technique uses Roland Barthes's Semiotic analysis, analyzing the meaning of signs through denotative, connotative, and mythical meaning systems. The data sources used are primary and secondary sources: primary sources are original data collected by the researcher, and secondary data is corroborating data used by the researcher. The results of the study indicate that: (1) the values ​​of Islamic religious education are present in the film. (2) The first Islamic educational values ​​are moral values, morals are divided into 2 parts, namely commendable morals and reprehensible morals, the commendable morals contained in the film include: birul waliadain, helping each other, giving gifts, advising, manners towards the opposite sex, reminding one's husband when he makes a mistake, visiting the sick, being serious. Next, there are reprehensible moral values: gossiping, being arrogant, being greedy, drinking alcohol, being hypocritical (3) there are values ​​of faith in it, including: seeking knowledge as a sign of deepening religious teachings, asking for guidance, spiritual closeness, guidance, believing in the power of Allah SWT.